2013
DOI: 10.1016/j.biomaterials.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photopolymerizable thiol-ene PEG and acrylate-based PEG hydrogels for cartilage development

Abstract: When designing hydrogels for tissue regeneration, differences in polymerization mechanism and network structure have the potential to impact cellular behavior. Poly(ethylene glycol) hydrogels were formed by free-radical photopolymerization of acrylates (chain-growth) or thiol-norbornenes (step-growth) to investigate the impact of hydrogel system (polymerization mechanism and network structure) on the development of engineered tissue. Bovine chondrocytes were encapsulated in hydrogels and cultured under free sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 45 publications
4
133
0
Order By: Relevance
“…In contrast, the phenotypes of chondrocytes encapsulated using a thiol-ene polymerization resemble those present in hyaline cartilage. 35 To investigate the effects of thiol-ene polymerizations on SMG cell viability, nongelling, thiol-ene polymerizations were performed using four-arm PEG-norbornene and the peptide KGKGKGKGCG (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the phenotypes of chondrocytes encapsulated using a thiol-ene polymerization resemble those present in hyaline cartilage. 35 To investigate the effects of thiol-ene polymerizations on SMG cell viability, nongelling, thiol-ene polymerizations were performed using four-arm PEG-norbornene and the peptide KGKGKGKGCG (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…27 PEG hydrogels are traditionally formed through radicalmediated photopolymerizations, 28,29 which allow for rapid fabrication into geometries dictated by custom molds in vitro or to match tissue defects in vivo. 30,31 PEG hydrogels have been utilized successfully to culture and control the behavior of various cell types, including MSCs, 32,33 chondrocytes, [34][35][36] osteoblasts, 37 pancreatic b-islet cells, 38,39 and neurons. 40,41 In addition, recent work has demonstrated the ability of PEG hydrogels to provide spatiotemporal control of MSC delivery in vivo to promote bone regeneration.…”
mentioning
confidence: 99%
“…PEGDA pre-polymer solutions were mixed to a final concentration of 10 wt% PEGDA ( M n ≈3400 Da, JenKem Technology, USA), 0.1 wt% LAP, and 5mM RGDS. The average molecular weight of each PEG chain was approximately conserved between PEGNB and PEGDA, and these materials have been shown to have similar mechanical properties 52,56-58 as hydrogels with comparative compositions. To characterize hydrogel microsphere size, a fluorescent dye, 0.01 wt% thiolated Rhodamine B, was added to and copolymerized with the hydrogel-forming solution to directly label the network.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps most importantly, PEGNB has been shown to support increased post-encapsulation viability over PEGDA for certain cell types, suggesting its broad utility as a cell encapsulant 50 . While the origins of PEGNB's increased cytocompatibility is unclear, studies have shown that PEGNB polymerization can be propagated by, thereby consuming, ROS 51,52 . For cell types that are especially sensitive to ROS, reducing these deleterious side products of photopolymerization may be a contributing factor to observed increasing cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In particular, thiol−ene photoclick chemistries have been used to generate hydrogel-based biomaterials with robust mechanical properties 5,9 and for the encapsulation of a wide variety of cell types, including, but not limited to, human mesenchymal stem cells (hMSCs), fibroblasts, chondrocytes, and pancreatic cells, with promise for cell culture and delivery. 10,11 Further, these chemistries have been used for the spatial patterning of biochemical cues to mimic key aspects of native cell microenvironments and facilitate appropriate cell-matrix interactions, including adhesion, differentiation, and invasion. 3,12 For the construction of thiol−ene hydrogels with light, peptides containing cysteines (thiol) commonly are reacted with polymers functionalized with acrylates or norbornenes ('ene') for rapid, photoinitiated polymerization under cytocompatible conditions.…”
Section: Introductionmentioning
confidence: 99%